97.9k views
1 vote
Hi plz help!!
find the value of p. (PLZ SHOW WORKINGS!!!)
-8p^2-4p+4​

User Shama
by
4.5k points

2 Answers

3 votes

Answer:

Simplifying

-8p2 + -4p = -4

Reorder the terms:

-4p + -8p2 = -4

Solving

-4p + -8p2 = -4

Solving for variable 'p'.

Reorder the terms:

4 + -4p + -8p2 = -4 + 4

Combine like terms: -4 + 4 = 0

4 + -4p + -8p2 = 0

Factor out the Greatest Common Factor (GCF), '4'.

4(1 + -1p + -2p2) = 0

Factor a trinomial.

4((1 + -2p)(1 + p)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(1 + -2p)' equal to zero and attempt to solve:

Simplifying

1 + -2p = 0

Solving

1 + -2p = 0

Move all terms containing p to the left, all other terms to the right.

Add '-1' to each side of the equation.

1 + -1 + -2p = 0 + -1

Combine like terms: 1 + -1 = 0

0 + -2p = 0 + -1

-2p = 0 + -1

Combine like terms: 0 + -1 = -1

-2p = -1

Divide each side by '-2'.

p = 0.5

Simplifying

p = 0.5

Subproblem 2

Set the factor '(1 + p)' equal to zero and attempt to solve:

Simplifying

1 + p = 0

Solving

1 + p = 0

Move all terms containing p to the left, all other terms to the right.

Add '-1' to each side of the equation.

1 + -1 + p = 0 + -1

Combine like terms: 1 + -1 = 0

0 + p = 0 + -1

p = 0 + -1

Combine like terms: 0 + -1 = -1

p = -1

Simplifying

p = -1

Solution

p = {0.5, -1}

Simplifying

-8p2 + -4p = -4

Reorder the terms:

-4p + -8p2 = -4

Solving

-4p + -8p2 = -4

Solving for variable 'p'.

Reorder the terms:

4 + -4p + -8p2 = -4 + 4

Combine like terms: -4 + 4 = 0

4 + -4p + -8p2 = 0

Factor out the Greatest Common Factor (GCF), '4'.

4(1 + -1p + -2p2) = 0

Factor a trinomial.

4((1 + -2p)(1 + p)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(1 + -2p)' equal to zero and attempt to solve:

Simplifying

1 + -2p = 0

Solving

1 + -2p = 0

Move all terms containing p to the left, all other terms to the right.

Add '-1' to each side of the equation.

1 + -1 + -2p = 0 + -1

Combine like terms: 1 + -1 = 0

0 + -2p = 0 + -1

-2p = 0 + -1

Combine like terms: 0 + -1 = -1

-2p = -1

Divide each side by '-2'.

p = 0.5

Simplifying

p = 0.5

Subproblem 2

Set the factor '(1 + p)' equal to zero and attempt to solve:

Simplifying

1 + p = 0

Solving

1 + p = 0

Move all terms containing p to the left, all other terms to the right.

Add '-1' to each side of the equation.

1 + -1 + p = 0 + -1

Combine like terms: 1 + -1 = 0

0 + p = 0 + -1

p = 0 + -1

Combine like terms: 0 + -1 = -1

p = -1

Simplifying

p = -1

Solution

p = {0.5, -1}

Explanation:

User Taazar
by
4.2k points
5 votes

Answer:

Explanation:

Simplifying

-8p2 + -4p = -4

Reorder the terms:

-4p + -8p2 = -4

Solving

-4p + -8p2 = -4

Solving for variable 'p'.

Reorder the terms:

4 + -4p + -8p2 = -4 + 4

Combine like terms: -4 + 4 = 0

4 + -4p + -8p2 = 0

Factor out the Greatest Common Factor (GCF), '4'.

4(1 + -1p + -2p2) = 0

Factor a trinomial.

4((1 + -2p)(1 + p)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(1 + -2p)' equal to zero and attempt to solve:

Simplifying

1 + -2p = 0

Solving

1 + -2p = 0

Move all terms containing p to the left, all other terms to the right.

Add '-1' to each side of the equation.

1 + -1 + -2p = 0 + -1

Combine like terms: 1 + -1 = 0

0 + -2p = 0 + -1

-2p = 0 + -1

Combine like terms: 0 + -1 = -1

-2p = -1

Divide each side by '-2'.

p = 0.5

Simplifying

p = 0.5

Subproblem 2

Set the factor '(1 + p)' equal to zero and attempt to solve:

Simplifying

1 + p = 0

Solving

1 + p = 0

Move all terms containing p to the left, all other terms to the right.

Add '-1' to each side of the equation.

1 + -1 + p = 0 + -1

Combine like terms: 1 + -1 = 0

0 + p = 0 + -1

p = 0 + -1

Combine like terms: 0 + -1 = -1

p = -1

Simplifying

p = -1

Solution

p = {0.5, -1}

Simplifying

-8p2 + -4p = -4

Reorder the terms:

-4p + -8p2 = -4

Solving

-4p + -8p2 = -4

Solving for variable 'p'.

Reorder the terms:

4 + -4p + -8p2 = -4 + 4

Combine like terms: -4 + 4 = 0

4 + -4p + -8p2 = 0

Factor out the Greatest Common Factor (GCF), '4'.

4(1 + -1p + -2p2) = 0

Factor a trinomial.

4((1 + -2p)(1 + p)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(1 + -2p)' equal to zero and attempt to solve:

Simplifying

1 + -2p = 0

Solving

1 + -2p = 0

Move all terms containing p to the left, all other terms to the right.

Add '-1' to each side of the equation.

1 + -1 + -2p = 0 + -1

Combine like terms: 1 + -1 = 0

0 + -2p = 0 + -1

-2p = 0 + -1

Combine like terms: 0 + -1 = -1

-2p = -1

Divide each side by '-2'.

p = 0.5

Simplifying

p = 0.5

Subproblem 2

Set the factor '(1 + p)' equal to zero and attempt to solve:

Simplifying

1 + p = 0

Solving

1 + p = 0

Move all terms containing p to the left, all other terms to the right.

Add '-1' to each side of the equation.

1 + -1 + p = 0 + -1

Combine like terms: 1 + -1 = 0

0 + p = 0 + -1

p = 0 + -1

Combine like terms: 0 + -1 = -1

p = -1

Simplifying

p = -1

Solution

p = {0.5, -1}

User Etgar
by
5.1k points